Work zones of Novi Sad (Vojvodina, Serbia) with examples of industrial transformation - Milošević Dragan D.; Đorđević Jasmina (Geographica Pannonica, 2015)
In this paper are presented historical industrial development and present industrial distribution in Novi Sad, the second largest city in the Republic of Serbia and the largest city of the Autonomous Province of Vojvodina. At present, industrial facilities in the city are located in work zones, at the entrance traffic routes to the city and the surrounding settlements, on individual sites within other city function areas or within the lots of family housing. Nevertheless, established work zones are main areas for industrial development of the city. Novi Sad has seven work zones: 'Sever I', 'Sever II', 'Sever III', 'Sever IV', 'Rimski Šančevi', 'Zapad' and 'Istok' that occupy 1761.9 ha. There are significant opportunities for economical development in these work zones, both on unconstructed surfaces and in the present complexes. Unfortunately, due to the crisis of industry in Serbia, numerous industrial facilities in the work zones of Novi Sad are neglected. In this paper are given examples of transformation of neglected industrial facilities and use of unconstructed area in work zone in Novi Sad. Transformation of industrial facilities within work zones is present in many cities (Budapest, Bucharest, Zagreb, Maribor, Milano, Krakow, New York) with positive examples.